ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP PEMBANGUNAN JALAN (STUDI KASUS: PERUMAHAN BHAYANGKARA PERMAI (POLDA) BUPER, KECAMATAN HERAM, KOTA JAYAPURA) - Samosir, Rasi Kasim; Siregar, Anggrainy Togi Marito; Purba, Rispah; Tommi, Tommi; Sitompul, Fanny Kristin Tantyah; Lubis, Rizal Arifin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: here has been no evaluation related to the level of public satisfaction with the construction of roads in the Bhayangkara Permai (Polda) Buper Waena housing complex RT 005 RW 001, Waena Village, Heram District, Jayapura City. This study aims to determine the level of public satisfaction with the construction of roads in the Bhayangkara Permai (Polda) Buper Waena housing complex, Waena Village, Heram District, Jayapura City. Data collection using saturated sampling techniques to 20 respondents who live in the Bhayangkara Permai (Polda) Buper Waena housing complex RT 005 RW 001, Waena Village, Heram District, Jayapura City. The research variables were compiled using the Kanzei method which was adjusted to the Public Satisfaction Index (IKM) variable of the Kepmen PAN Number 25 of 2004. The measurement results obtained the overall service element was very satisfied with an average of 3,575. Based on the results obtained,